Health-Related Cognitions and Metacognitions Indirectly Contribute to the Relationships Between Impulsivity, Fear of COVID-19, and Cyberchondria - Eskisu, Mustafa; cam, Zekeriya; Boysan, Murat (Springer, 2023)
The aim of the study was to converge a structural equation model to unfold the compositive relationships between trait impulsivity, health cognitions, metacognitions about health, fear of COVID-19 and cyberchondria, after controlling for gender, age, marital status, having a chronic illness and chronic illness among first-degree relatives. Six hundred fifty-one participants (423 females, 65%; 228 males, 35%) participated in the study. The Short UPPS-P Impulsive Behavior Scale (S-UPPS-P), Health Cognitions Questionnaire (HCQ), The Meta-Cognitions about Health Questionnaire (MCQ-HA), Cyberchondria Severity Scale -Short Form (CSS-12), and Fear of COVID-19 Scale (FCV-19 S) were completed by volunteered participants. The structural model showed that the S-UPPS-P directly and indirectly contributed to the HCQ, MCQ-HA, CSS-12, and FCV-19 S. The multi-group structural analysis by gender showed that the structural model had a partial measurement and factorial invariance. We concluded that the significant associations between impulsivity, fear of COVID-19 and cyberchondria were indirectly contributed by health-related cognitions and metacognitions.
Keywords: Impulsivity; Cyberchondria; Metacognitions; Fear Of Covid-19; Measurement Invariance; Of-Fit Indexes; Sensation Seeking; Initial Validation; Emotion Regulation; Anxiety; Gender; Model; Expectancies; Metaanalysis; Depression